Konsep Keselamatan di Dalam Yesus: Ketaatan Pada Firman Versus Ketaatan Pada Perbuatan - Sutriatmo Sutriatmo (Jurnal Teologi Berita Hidup, 2022)
It is often heard that salvation is not properly understood. Many Christians think that when they “believe” in the Lord Jesus, they are Christians, they feel they have been saved. But if you see his life is not in accordance with God’s will (disobedience). There are Christians who still go to witch a shaman. People who already believe in the Lord Jesus should not go to a shaman to seek escapism in their business, to get blessings, to survive or to secure their business, this is not in accordance with the teachings of salvation. in the Lord Jesus. Someone must obey according to the teachings of God's word, love God with all his heart, whole soul, and all mind. Because it is clear that the act is idolatry. How is the concept of salvation based on God's word versus based on actions? This is what needs to be researched, and straightened out, so that God’s people have the correct concept of teaching salvation. The purpose of this research is for Christians to have an understanding of the concept of salvation in the Lord Jesus Christ, and obedience to God's word, rather than just human actions or efforts that are not in accordance with God's word. Meanwhile, in Ephesians 2: 8-9 it says, “For it is by grace you have been saved, through faith—and this is not from yourselves, it is the gift of God not by works, so that no one can boast." Many Christians regard good works as a condition for being saved. But the truth is because of His grace a person can be saved by faith, and not human works or works. As for a person's good deeds are proof that he has faith. True faith must be demonstrated in the works of faith and in the righteousness of the Lord Jesus Christ.  Sering didengar bahwa keselamatan kurang dipahami secara benar. Banyak orang Kristen mengira bahwa ketika “sudah percaya” Tuhan Yesus, sudah beragama Kristen, merasa sudah diselamatkan. Namun kalau dilihat kehidupannya belum sesuai dengan kehendak Allah (tidak taat). Ada orang Kristen yang masih pergi ke dukun. SeseorangyangsudahpercayaTuhanYesusmakatidakdiperkenankankedukunmencari pelarisandalamusahanya, agar berolehberkat,agar selamatatauamanusahanya,halinitidak sesuaidenganpengajarankeselamatandidalamTuhanYesus. Seseorangharus taatsesuaiajaran firmanTuhan,mengasihiTuhandengansegenaphati,segenapjiwa,dansegenapakalbudi.Karena jelas bahwatindakan tersebut adalah penyembahan berhala. Bagaimanakah konsep keselamatan berdasarkan firman Tuhan versus berdasarkan perbuatan ? Hal inilah yang perlu diteliti, dan diluruskan, sehingga umat Tuhan memiliki konsep pengajaran keselamatan yang benar. Tujuan dari penelitian ini adalah agar orang Kristen memiliki pemahaman tentang konsep keselamatan di dalam Tuhan Yesus Kristus, dan ketaatan pada firman Tuhan, dibandingkan hanya perbuatan atau usaha manusia yang tidak sesuai dengan firman Tuhan. Sedangkan dalam Efesus 2:8-9 dikatakan bahwa, “Sebab karena kasih karunia kamu diselamatkan oleh iman; itu bukan hasil usahamu, tetapi pemberian Allah, itu bukan hasil pekerjaanmu: jangan ada orang yang memegahkan diri.” Banyak orang Kristen menganggap bahwa perbuatan baik sebagai syarat untuk dapat diselamatkan. Namun yang benar adalah oleh karena kasih karuniaNya seseorang dapat diselamatkan oleh iman, dan bukan usaha atau pekerjaan manusia. Adapun perbuatan-perbuatan baik seseorang adalah sebagai bukti bahwa ia memiliki iman. Iman yang benar harus ditunjukkan dalam perbuatan-perbuatan iman dan dalam kebenaran Tuhan Yesus Kristus.